R-Regular Integers Modulo - Rao, M. Ganeshwar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Introducing the notion of ar-regular integer modulo we obtain some basic properties of such integers and arithmetic properties of certain functions related to them.